The effects of smoking norms and attitudes on quitting intentions in Malaysia, Thailand and four Western nations: A cross-cultural comparison - Warwick Hosking (2018)
This research investigated the influence of smoking attitudes and norms on quitting intentions in two predominantly collectivistic countries (Malaysia and Thailand) and four predominantly individualistic Western countries (Canada, USA, UK and Australia). Data from the International Tobacco Control Project (N = 13,062) revealed that higher odds of intending to quit were associated with negative personal attitudes in Thailand and the Western countries, but not in Malaysia; with norms against smoking from significant others in Malaysia and the Western countries, but not in Thailand; and with societal norms against smoking in all countries. Our findings indicate that normative factors are important determinants of intentions, but they play a different role in different cultural and/or tobacco control contexts. Interventions may be more effective if they are designed with these different patterns of social influence in mind.